Distributions of NO, NOx , and NOy in the upper troposphere and lower stratosphere between 28° and 61°N during POLINAT 2 - Ziereis, H.; Schlager, H.; Schulte, P.; van Velthoven, P.F.J.; Slemr, F. (Journal of Geophysical Research: Atmospheres, 2000)
During the Pollution From Aircraft Emissions in the North Atlantic Flight Corridor 2 (POLINAT 2) field campaign the distribution of NO, NOx , and NOy in the upper troposphere and lowermost stratosphere over the eastern North Atlantic was measured using the Deutsches Zentrum für Luft- und Raumfahrt research aircraft Falcon. Based from Shannon Airport in Ireland, 14 flights were carried out between September 19 and October 25, 1997. The measurements were performed in and out of the North Atlantic flight corridor covering latitudes between 28°N and 61°N. A marked latitudinal gradient in NO, NOx , and NOy , the sum of all reactive nitrogen compounds, was observed. Mean NO volume mixing ratios in the upper troposphere increased from about 50 parts per trillion by volume (pptv) at 28°N to about 180 pptv at 59°N. A similar latitude dependence was also found for NO x and NO y . In the northern part of the POLINAT 2 measuring area, NO and NO x volume mixing ratios increased significantly with increasing altitude withmaximum values around the tropopause, while in the southern part of the measuring area no strong altitude gradient was observed. NO and NOx did not show a substantial gradient across the tropopause. NO/NOy and NOy /O3 ratios showed maximum values of about 0.30 ppbv/ppbv and 0.012 ppbv/ppbv, respectively, around the tropopause. The POLINAT 2 observations suggest that aircraft emissions are an important source of NOx and NOy in the region studied. Also, the present measurements contribute to the data set obtained in the North Atlantic flight corridor during the last few years and help to establish a NOx climatology around the tropopause for this region.